Cidades conectadas: a comunicação e as tecnologias móveis reconfigurando o espaço urbano - Gonçalves, Ricardo Basilio (2013)
This dissertation has as object of study the "Connected Cities", with the overall goal of the research to identify and understand how ICT Information and Communication Technologies reconfigured the urban space, generating significant effects on contemporary society. The development of the concept and the function of "town" are studied, and analyzed also the social and natural performances. It investigates the relationship between urban space and virtual space and how this interconnection (physical and digital space) generated effects in society, specifically in the way people organize themselves and socialize in urban space, creating some concepts, including the concept of "cybercity". It analyzes through references, the concepts of "cyberspace" and collective intelligence propagated by Pierry Lévy, André Lemos, among other researchers. It investigates also cases prepared by Massachusetts Institute of Technology MIT, working with the research theme "smart cities", presenting the most varied possibilities of interference in urban space through ICTs. Solutions are also analyzed from the new technologies of information and communication that interfere in the daily lives of people in the cities. The theme "connected cities" becomes, well, a relevant study to the area of communication, in which researchers discuss its evolution linked to new technologies, and observe, through scientific research, numerous mutations in contemporary society to the issue forward. It concludes that, in citizens lives, mobility in the ICTs age is an important, irreversible and extremely necessity for people to remain "alive" in the virtual and urban space, searching for their identities, their ideals, their freedom expression and finding solutions to various problems presented in this society, which lives and remains network